Exploring the impact and experience of fractional work in medicine: a qualitative study of medical oncologists in Australia. Issue 12 (10th December 2019) - Kirby, Emma; Broom, Alex; Karikios, Deme; Harrup, Rosemary; Lwin, Zarnie
Abstract : Objectives: Fractional (part-time) appointments are becoming more commonplace in many professions, including medicine. With respect to the contemporary oncological landscape, this highlights a critical moment in the optimisation of employment conditions to enable high-quality service provision given growing patient numbers and treatment volume intensification. Data are drawn from a broader study which aimed to better understand the workforce experiences of medical oncologists in Australia. This paper specifically aims to examine a group of clinicians' views on the consequences of fractional work in oncology. Design: Qualitative, one-on-one semistructured interviews. Interview transcripts were digitally audio recorded and transcribed verbatim. Data were subject to thematic analysis supported by the framework approach and informed by sociological methods and theory. Setting: New South Wales, Australia. Participants: Medical oncologists (n=22), including 9 female and 13 male participants, at a range of career stages. Results: Four key themes were derived from the analysis: (1) increasing fractional employment relative to opportunities for full-time positions and uncertainty about future opportunities; (2) tightening in role diversity, including reducing time available for research, mentoring, professional development and administration; (3) emerging flexibility of medical oncology as a specialty and (4) impact of fractional-as-norm on workforce sustainability and quality of care. Conclusion: Fractional appointments are viewed as increasing in oncology and the broader consequences of this major shift in medical labour remain unexamined. Such appointments offer potential for flexible work to better suit the needs of contemporary oncologists; however, fractional work also presents challenges for personal and professional identity and vocational engagement. Fractional appointments are viewed as having a range of consequences related to job satisfaction, burnout and service delivery. Further research is needed to provide a critical examination of the multiple impacts of workforce trends within and beyond oncology.